A vaccinia-based single vector construct multi-pathogen vaccine protects against both Zika and chikungunya viruses - Natalie A. Prow (Nature Portfolio, 2018)
Zika and chikungunya virus are co-circulating in many regions and currently there is no approved vaccine for either virus. Here, the authors engineer one vaccinia virus based vaccine for both, Zika and chikungunya, and show protection from infection and pathogenesis in mice.